Preoperative Radiation Therapy Followed by Reexcision May Improve Local Control and Progression-Free Survival in Unplanned Excisions of Soft Tissue Sarcomas of the Extremity and Chest-Wall. (10th October 2016) - Saeed, Hina; King, David M.; Johnstone, Candice A.; Charlson, John A.; Hackbarth, Donald A.; Neilson, John C.; Bedi, Manpreet
Abstract : Background . The management for unplanned excision (UE) of soft tissue sarcomas (STS) has not been established. In this study, we compare outcomes of UE versus planned excision (PE) and determine an optimal treatment for UE in STS. Methods . From 2000 to 2014 a review was performed on all patients treated with localized STS. Clinical outcomes including local recurrence-free survival (LRFS), progression-free survival (PFS), and overall survival (OS) were evaluated using the Kaplan-Meier estimate. Univariate (UVA) and multivariate (MVA) analyses were performed to determine prognostic variables. For MVA, Cox proportional hazards model was used. Results . 245 patients were included in the analysis. 14% underwent UE. Median follow-up was 2.8 years. The LR rate was 8.6%. The LR rate in UE was 35% versus 4.2% in PE patients (p < 0.0001 ). 2-year PFS in UE versus PE patients was 4.2 years and 9.3 years, respectively (p = 0.08 ). Preoperative radiation (RT) (p = 0.01 ) and use of any RT for UE (p = 0.003 ) led to improved PFS. On MVA, preoperative RT (p = 0.04 ) and performance status (p = 0.01 ) led to improved PFS. Conclusions . UEs led to decreased LC and PFS versus PE in patients with STS. The use of preoperative RT followed by reexcision improved LC and PFS in patients who had UE of their STS.